Level-crossing intensity for the density of the image of the Lebesgue measure under the action of a Brownian stochastic flow - Fomichev, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We compute the level-crossing intensity for the density of the image of the Lebesgue measure under the action of a Brownian stochastic flow, which is a smooth approximation of the Arratia flow, and determine its asymptotic behavior as the height of the level tends to infinity.